3,3'-Diindolylmethane enhances apoptosis in docetaxel-treated breast cancer cells by generation of reactive oxygen species - Susan Lanza-Jacoby; Guanjun Cheng (Taylor & Francis Group, 2018)
Context: A major problem in the treatment of cancer is the development of toxic side effects and resistance to chemotherapy. The use of plant compounds to overcome resistance and prevent toxicity is a potential strategy for treatment. Objective: We evaluated whether 3,3'-diindolylmethane (DIM) enhanced the sensitivity of breast cancer cells to docetaxel (DOC). Materials and methods: MDA-MB231 and Sk-BR-3 cells were treated with and without 25 or 50 µM of DIM and 1 nM of DOC for 48 and 72 h, respectively. MTT assay was used to measure cell survival. Apoptosis and intracellular reactive oxygen species (ROS) were determined by flow cytometry. The expression of proteins regulating ROS production and apoptosis was evaluated by immunoblotting technique. Results: Combining 25 µM of DIM with 1 nM DOC decreased cell survival by 42% in MDA-MB231 cells and 59% in Sk-BR-3 cells compared to control, DIM, or DOC (p ≤ 0.05). The combination treatment increased apoptosis over 20% (p ≤ 0.01) in both cell lines, which was associated with decreased Bcl-2, increased Bax, cleaved PARP and activated JNK (p ≤ 0.01). ROS production increased by 46.5% in the MDA-MB231 and 29.3% in Sk-BR-3 cells with the combination compared to DIM or DOC alone. Pretreating cells with N-acetyl-cysteine or Tiron abrogated the anti-survival effect of the combination. The increase in ROS was associated with a 54% decrease in MnSOD and 47% increase in NOX2 protein compared to the other groups. Conclusions: Our findings indicated that DIM enhances the sensitivity of breast cancer cells to DOC treatment by increasing ROS, which led to decreased cell survival and apoptosis.